DYSLIPIDEMIA MANAGEMENT THROUGH THE SIDDHA FORMULATION CAPSULE ARJUN FORTE - A CASE SERIES - P, Nirmala Devi.; C. B. S, Bharath Christian; S, Ethel Shiny.; M, Vanitha. (Journal of Global Pharma Technology, 2024)
Siddha medicine is an ancient traditional system of medicine healing 4448 diseases in the southern part of India, especially Tamilnadu, Srilanka and Malaysia. Dyslipidemia is a condition which is associated with several morbid manifestations. Generally, dyslipidemia does not have any obvious symptoms but they are usually discovered at routine investigation. But it is a leading cause of death due to atherosclerosis, myocardial infarction and ischemic stroke. Purpose of the study was to treat dyslipidemia with Arjun forte capsule, Siddha oral medicine. Here we present a case that was success with siddha management. Four female patients came to my outpatient department of Santhigiri Siddha Medical College and Hospital, Trivandrum, Kerala, with complaints of difficulty in breathing, no other chronic illness such as Diabetes mellitus/Hypertension. The Lab primary report revealed high levels of serum cholesterol LDL, and Triglycerides. No treatment has been taken so far regarding this issue. I was given 2month treatment of capsule Arjun Forte as an internal medicine along with diet and lifestyle modifications. Excellent results observed ultimately. The amount of lipids in blood came to normal in a lab report and symptoms of difficulty in breathing at night were completely relieved. So, It could be concluded as efficacy of Arjun Forte excellent in treating dyslipidemia. Keywords: Siddha management, Dyslipidemia, Capsule-arjun forte, Specific diet, Metabolic dysfunction, Lifestyle disorders, Herbo mineral drug.